ASSESMENT OF SATISFACTION AND BUSINESS IMAGE OF ALSINTAN SERVICES (UPJA) NUSANTARA IN DLEMER VILLAGE, AROSBAYA DISTRICT, BANGKALAN REGENCY - Rifatul Husnia; Teti Sugiarti (Agriscience, 2021)
In Madura, especially in the area of Bangkalan Regency, to increase agricultural productivity and overcome the problem of declining agricultural workforce, the central government through Dispertahorbun Bangkalan distributes equipment and agricultural machinery assistance to farmers by forming an Alsintan Service Unit (UPJA). This study aims to analyze, (1) Assessment of farmer satisfaction with services and use of Nusantara alsintan services in Dlemer; (2) Image evaluation on services and use of UPJA Nusantara in Dlemer; (3) Relationship between Nusantara Alsintan service satisfactions with UPJA Nusantara's image in Dlemer. The method used in this research is quantitative and correlations analysis. The results showed that the assessment of farmer satisfaction with services and use of Nusantara alsintan services in Dlemer was in the satisfied category. Indicators of responsiveness, reliability, assurance, and emphaty are in the category of satisfaction, while the tangible is in the category of quite satisfied. The image assessment on the service and use of UPJA Nusantara in Dlemer, there are several indicators including social responsibility, innovation, management quality, and community trust all in the good category. The relationship between Nusantara service satisfaction and UPJA Nusantara's image in Dlemer has a positive relationship between Nusantara service satisfaction and UPJA Nusantara's image.Keywords: UPJA, Satisfaction, Image, Correlation.